The Analysis Of Services Quality, Facilities And Infrastructure, And Their Effect On Consumer Loyalty In The New Normal (Case Study: Hospitality Industry In Banda Aceh) - Indra Akbar; Ricky Ariansyah (Jurnal Mantik, 2021)
The purpose of this study is to analyze: (1) service quality, (2) facilities and infrastructure, (3) consumer satisfaction, and (4) its impact on consumer loyalty in the New Normal in Banda Aceh. The data collection method is a simple random sampling technique, with data analysis using path analysis. The samples are 120 respondents. The results of the analysis show that there is the direct influence of service quality (0.617) and facilities and infrastructure on consumer loyalty (0.372); the acquisition value is higher than the indirect effect of service quality on consumer loyalty with purchasing decisions as an intervening variable (0.026) and facilities and infrastructure on consumer loyalty with customer satisfaction as an intervening variable (0.010). The structural equations in this study are: Consumer satisfaction = 0.745 Service Quality + 0.281 facilities and infrastructure. Consumer loyalty = 0.035 Consumer satisfaction + 0.617 Quality of service + 0.372 facilities and infrastructure. From the results of the study, all variables show a very significant effect on consumer loyalty except for the variable of customer satisfaction on customer loyalty which was not significant. It means that every customer satisfaction will not necessarily lead to consumer loyalty.